Effects of bariatric surgery on non-alcoholic fatty liver disease: magnetic resonance imaging is an effective, non-invasive method to evaluate changes in the liver fat fraction - Hedderich, Dennis M.; Schönberg, Stefan; Otto, Mirko (Obesity surgery, 2017)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is considered the most common liver disease worldwide and is highly associated with obesity. The prevalences of both conditions have markedly increased in the Western civilization. Bariatric surgery is the most effective treatment for morbid obesity and its comorbidities such as NAFLD. Objectives: Measure postoperative liver fat fraction (LFF) in bariatric patients by using in-opposed-phase MRI, a widely available clinical tool validated for the quantification of liver fat. Methods: Retrospective analyses of participants, who underwent laparoscopic Roux-Y-gastric-bypass (17) or laparoscopic sleeve gastrectomy (2) were performed using magnetic resonance imaging (MRI), bioelectrical impedance analysis (BIA), and anthropometric measurements 1 day before surgery, as well as 6, 12, and 24 weeks after surgery, LFF was calculated from fat-only and water-only MR images. Results: Six months after surgery, a significant decrease of LFF and liver volume has been observed along with weight loss, decreased waist circumference, and parameters obtained by body fat measured by BIA. LFF significantly correlated with liver volume in the postoperative course. Conclusions: MRI including in-opposed-phase imaging of the liver can detect the quantitative decrease of fatty infiltration within the liver after bariatric surgery and thus could be a valuable tool to monitor NAFLD/NASH postoperatively.